Not if, but when we need resilience in the workplace. (18th November 2015) - King, Danielle D.; Newman, Alexander; Luthans, Fred
Summary: Workplace resilience is a necessity for organizations and employees given it assists them in overcoming adversity and ultimately succeeding. However, organizational scholars have largely overlooked this construct. In this Incubator, we briefly summarize extant research on workplace resilience to highlight opportunities for theory building and advancement of empirical research. Copyright © 2015 John Wiley & Sons, Ltd.